Analysis Of The Utilization Of Plastic Waste As A Basic Material For Making Bags - Ratnawati Ratnawati (Abdimas Paspama, 2024)
The increasing increase in plastic waste from households will become a serious problem if a solution is not found. On the one hand, the discovery of plastic has had an extraordinary positive impact, because plastic has advantages over other materials. Based on the large amount of plastic waste, this activity needs to be carried out with the aim of improving the community's economy. This means creating new, innovative jobs from the development of household industries. The next stage of the plan is assistance in processing plastic waste into products so that standard quality and quantity of products are obtained, as well as program evaluation to see how far this program is beneficial for everyone.